PEREKONOMIAN DESA SUKA DAMAI KECAMATAN MESTONG KABUPATEN MUARO JAMBI 1983-2015 - Erika Melyani Siti Heidi Karmela (Universitas Batanghari Jambi, 2019)
AbstractEconomic activity is a supporter of the development and progress of a region. Likewise in Suka Damai Village which continues to show the development of economic activity from year to year. The agricultural sector, animal husbandry, small business trade, plantations and small industries are the cornerstone of ways for the Suka Damai Village community to fulfill their needs. Some economic sectors in Suka Damai Village experienced changes in the economic system from traditional economic systems to modern economic systems. It can be seen from the supporting tools of the economic activities of the population that they have begun to use heavy equipment such as evcavators, tractors, commpressos. In addition to the landowners have begun to use labor services to help ease their work and to help harvest agricultural and plantation products belonging to farmers. Furthermore, for small businesses themselves, they have used labor such as employees and mechanics. The shape of the building has begun to be permanent (shop). Small and Medium Industries / making tempeh and furniture began to develop where as business actors were IRTs. This shows economic progress in Suka Damai Village.Keywords: Village Economic Sector, Residents of Suka Damai Village AbstrakAktivitas perekonomian merupakan pendukung perkembangan dan kemajuan suatu daerah.Begitu juga di Desa Suka Damai yang terus memperlihatkan perkembangan aktivitas perekonomian dari tahun ke tahunnya.Sektor pertanian, peternakan, perdagangan usaha kecil, perkebunan dan industri kecil menjadi tumpuan cara bagi masyarakat Desa Suka Damai dalam memenuhi kebutuhan hidupnya. Beberapa sektor ekonomi di Desa Suka Damai mengalami perubahan sistem ekonomi dari sistem ekonomi tradisional menjadi sistem ekonomi modern.Hal tersebut dilihat dari alat-alat pendukung aktivitas perekonomian penduduk sudah mulai menggunakan alat berat seperti evcavator, traktor, commpresso. Selain itu para pemilik lahan sudah mulai menggunakan jasa tenaga kerja untuk membantu meringankan pekerjaannya dan untuk membantu panen hasil pertanian dan perkebunan milik petani.Selanjutnya untuk usaha kecil sendiri, sudah memakai tenaga kerja seperti karyawan dan montir.Bentuk bangunan pun sudah mulai permanen (ruko). Industri Kecil Menengah / pembuatan tempe dan mebel mulai berkembang dimana sebagai pelaku usahanya adalah para IRT. Hal tersebut menunjukkan kemajuan ekonomi di Desa Suka Damai.Kata Kunci : Sektor Perekonomi Desa, Penduduk Desa Suka Damai